COMMANDING AND FORBIDDING THE IMAM: A STUDY OF THE CONCEPT OF AL-AMR BI AL-MA'RUF AND AL-NAHY 'AN AL-MUNKAR IN ISLAMIC IMAMSHIP - Mohd Sharif, Mohd Farid (Jurnal Syariah, 2008)
The notion of commanding right and forbidding wrong is one of the notable values in Islam. This has been emphasized in verse 104 of surah Ali 'Imran [3]: "Let there arise out of you a group of people inviting to all that is good, enjoining right and forbidding wrong". This article is about the imam as an agent of forbidding wrong and as an agent of wrongdoing. It aims to make an important contribution to the study of administrative ethics in Islamic imamship. It explains how the imam plays its role in the society as of commanding good and forbidding wrong. It also examines the wrongdoing of imams and the ethics of commanding and forbidding the imam.